MEMBANGUN KESADARAN TERHADAP KESEJAHTERAAN DIGITAL MELALUI SLOGAN DALAM BAHASA INGGRIS KEPADA SISWA MAS ALWASHLIYAH GEDUNG JOHOR MEDAN - Fransiska, Widia; Zulkarnain, Iskandar; Sihite, Meida Rabia; Rangkuti, Linda Astuti; Nasution, Putra Thoip; Rafikah, Rafikah (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
The use of technology is inseparable from the daily lives of students in Indonesia, but many still overlook the importance of possessing good digital well-being. This community service activity aims to raise students’ awareness of digital well-being through slogans in English. The community service was carried out at MAS Alwashliyah Gedung Johor for the tenth-grade students, involving 5 lecturers and 1 university student. The survey shows that most students are not yet aware of the importance of performing good digital well-being practice. In this workshop, students received information about digital-wellbeing and contributed to raising awareness among the community through slogans about digital well-being in English. The community service activity received positive feedback from students, as evidenced by the positive notes shared by students after participating in this workshop.